ASSESSING THE VOCABULARY SIZE OF THE INTERNATIONAL CLASS STUDENTS - Vinindita Citrayasa; Maria Setyaningsih Nernere (Universitas PGRI Yogyakarta, 2020)
As the important component of language acquisition and language learning affecting language skill mastery, vocabulary has been the concern of the language expertise. Many of them focus a lot on how to enrich the learners’ vocabulary. In fact, vocabulary development is not only about increasing the quantity but also on its quality. Knowing this fact, it is needed to find out how qualified the vocabulary development nowadays. Therefore, the quantitative study is done to identify and analyze the vocabulary size developmental pattern across the levels. It is a cross sectional survey research. The data was taken by doing vocabulary test to the international students who deal a lot with English exposure in their learning. Three batches consisting of freshmen, sophomore, and junior in the International classes were assessed to see their developmental pattern. Vocabulary size test developed by Paul Nation becomes the best option as the test measuring the vocabulary size of the students. As a result, the hypothesis was accepted. It is found that there is a difference in the vocabulary size from the three batches with a surprising finding too due to the pattern. This result is then useful for a means of reflection and evaluation for the students and the institution.